Genotypic Detection of Carbapenem-Resistant Escherichia Coli Producing NDM-1 Gene for the First Time in Baghdad/Iraq - Nadheema Hammood Hussein (Journal of Global Pharma Technology, 2017)
For the first time, this study reports the presence of New Delhi Metallo-β-Lactamase gene (NDM-1 gene) among Carbapenem resistant Escherichia coli (E. coli) isolates in Baghdad / Iraq. Sixty six E. coli clinical isolates were collected from Baghdad Teaching Hospital/ Medical city in Baghdad. The isolates were obtained from different clinical specimens including urine, wound swabs, sputum and blood. All isolates were identified by Vitek-2 system and the susceptibility test to different antibiotics was also done by Vitek-2 system.  The results showed most isolates under the study were multidrug resistance and all 66 E. coli isolates had 100% resistance to Ampicillin. The most effective antibiotic against E. coli isolates was Imipenem followed by Amikacin. The results also showed that 5 (7.6%) isolates out of 66 E. coli were resist for Imipenem (Carbapenem resistant E. coli isolates).  By using conventional PCR, the blaNDM-1 gene was detected in 2 (40%) isolates, out of 5 Carbapenem resistant E. coli isolates and the3 (60%) isolates of Carbapenem resistant E. coli don’t harboring bla NDM-1 gene. Sequencing of (983 bp) blaNDM-1 amp icon was carried out by Macrogen DNA Sequencing and aligning of the obtained sequences with the reference strains in Gen Bank confirmed the correct identification of blaNDM-1 in Carbapenem resistant E. coli. The data sequencing revealed (100%) homology with reference strains in Gen Bank and the data of blaNDM-1 sequencing was submitted to the Gen Bank of the National Center for Biotechnology Information (NCBI) under the accession number (KY966040).Keywords: Escherichia coli, Carbapenem resistance and bla NDM-1 gene genes.